Glutaminase 2 stabilizes Dicer to repress Snail and metastasis in hepatocellular carcinoma cells. Issue 2 (28th December 2016) - Kuo, Tsang-Chih; Chen, Chi-Kuan; Hua, Kuo-Tai; Yu, Pei; Lee, Wei-Jiunn; Chen, Min-Wei; Jeng, Yung-Ming; Chien, Ming-Hsien; Kuo, Kuang-Tai; Hsiao, Michael; Kuo, Min-Liang
Abstract: Glutaminolysis that catabolizes glutamine to glutamate plays a critical role in cancer progression. Glutaminase 2 (GLS2) has been reported as a tumor suppressor. Recent studies implied that GLS2 may display its multifunction besides classical metabolic feature by different localizations and potential protein binding domains. Here, we showed that GLS2 expression correlates inversely with stage, vascular invasion, tumor size and poor prognosis in human hepatocellular carcinoma (HCC) tissues. We found that GLS2 significantly represses cell migration, invasion and metastasis of HCC through downregulation of Snail in vitro and in vivo . Moreover, our results demonstrated that GLS2 interacts with Dicer and stabilizes Dicer protein to facilitate miR-34a maturation and subsequently represses Snail expression in a glutaminase activity independent manner. Our findings indicate that non-glutaminolysis function of GLS2 inhibits migration and invasion of HCC cells by repressing the epithelial–mesenchymal transition via the Dicer-miR-34a-Snail axis.